The evolving ethics of analysis, publication, and transparency in applied economics. Issue 4 (29th December 2020) - Lybbert, Travis J.; Buccola, Steven T.
Abstract: Credible economic research demands discipline and defensible modeling assumptions—both theoretical and empirical—but incentives to strategically shape findings (e.g., p‐ hack) can be strong. We examine recent waves of empiricism in economics and the ethical concerns and responses they prompted. Statistical abuses that opportunistically search for significance are often inseparable from conceptual abuses of opportunistic model identification (i.e., p‐hacking writ large ). We compare neoclassical with positivist hacking proclivities and explore associated implications for empirical analysis and peer review. Drawing on our experiences, 25 years apart, as AJAE editors we reflect on efforts to evaluate research quality and enhance research transparency. Abstract : Related Content: What Do you Mean by "Informed Consent"? Ethics in Economic Development Research Related Content: Research ethics beyond the IRB: Selection bias and the direction of innovation in applied economics Related Content: Ulysses' pact or Ulysses' raft: Using pre-analysis plans in experimental and nonexperimental research